Usual and unusual pitfalls of 18F-FDG-PET/CT in lymphoma after treatment: a pictorial review. Issue 7 (July 2017) - Dubreuil, Julien; Salles, Gilles; Bozzetto, Juliette; Tordo, Jeremie; Djaïleb, Loïc; Berriolo-Riedinger, Alina; Leenhardt, Julien; Giammarile, Francesco; Meignan, Michel; Skanjeti, Andrea
Abstract : Fluorine-18-fluorodeoxyglucose ( 18 F-FDG) PET/computed tomography (CT) is now a standard of care in initial staging and treatment evaluation of lymphomas. It is also used in the interim evaluation in diffuse large B cell lymphoma and Hodgkin lymphoma. However, several pitfalls may occur during or after treatment, because of the nonspecificity of 18 F-FDG for lymphoma disease and treatment as immunotherapy, thus possibly induces misinterpretation and wrong treatment decision. The aim of this pictorial review is to provide an illustrated tutorial of the most frequent pitfalls found on 18 F-FDG-PET/CT during or after treatment.